POTENSI LAHAN SAWAH UNTUK PENGEMBANGAN TANAMAN TEMBAKAU DI KABUPATEN BONDOWOSO - Budiman, Subhan Arif; Maulia, Dina; Hermiyanto, Bambang; Basuki, Basuki (Jurnal Tanah dan Sumberdaya Lahan, 2024)
The plantation sector, especially tobacco plants, is the biggest contributor to the country's foreign exchange value non-mining through tobacco excise and export. With the increasing number of active smokers in Indonesia, the need for tobacco continues to increase, emphasizing the role of this crop in the economy and providing large profits for farmers. However, along with the growing issue of land use change, recently many tobacco plants have been planted on unsuitable land. The research was conducted on all rice fields in Bondowoso Regency from October 2022 to March 2023. The land suitability evaluation method was used to assess land characteristics that affect tobacco plant growth. The parameters used were soil pH, soil texture, C-organic, electrical conductivity, cations bases (K, Ca, Na, Mg), cation exchange capacity (CEC), base saturation, total N, available and exchangeable K, slope, temperature, and rainfall. Data analysis was carried out by matching techniques, namely matching land characteristics with the growing conditions of tobacco plants to get some suitable land suitability classes for tobacco plants. The results of the analysis showed that the area of ​​land currently planted with tobacco reaches about 12,155.06 hectares, with a suitable class (S2) reaching 897.82 hectares, marginal (S3) reaching 1,614.44 hectares, and not suitable (N) reaching 9,642.79 hectares. Land that has the potential to grow tobacco is S2 (quite suitable) and S3 (marginal).